CCR2‐dependent Gr1high monocytes promote kidney injury in shiga toxin‐induced hemolytic uremic syndrome in mice. Issue 6 (16th April 2018) - Pohl, Judith‐Mira; Volke, Julia K.; Thiebes, Stephanie; Brenzel, Alexandra; Fuchs, Kerstin; Beziere, Nicolas; Ehrlichmann, Walter; Pichler, Bernd J.; Squire, Anthony; Gueler, Faikah; Engel, Daniel R.
Abstract: The hemolytic uremic syndrome (HUS) is a life‐threatening disease of the kidney that is induced by shiga toxin‐producing E.coli . Major changes in the monocytic compartment and in CCR2‐binding chemokines have been observed. However, the specific contribution of CCR2‐dependent Gr1 high monocytes is unknown. To investigate the impact of these monocytes during HUS, we injected a combination of LPS and shiga toxin into mice. We observed an impaired kidney function and elevated levels of the CCR2‐binding chemokine CCL2 after shiga toxin/LPS‐ injection, thus suggesting Gr1 high monocyte infiltration into the kidney. Indeed, the number of Gr1 high monocytes was strongly increased one day after HUS induction. Moreover, these cells expressed high levels of CD11b suggesting activation after tissue entry. Non‐invasive PET‐MR imaging revealed kidney injury mainly in the kidney cortex and this damage coincided with the detection of Gr1 high monocytes. Lack of Gr1 high monocytes in Ccr2 ‐deficient animals reduced neutrophil gelatinase‐associated lipocalin and blood urea nitrogen levels. Moreover, the survival of Ccr2 ‐deficient animals was significantly improved. Conclusively, this study demonstrates that CCR2‐dependent Gr1 high monocytes contribute to the kidney injury during HUS and targeting these cells is beneficial during this disease. Abstract : This study shows the critical contribution of Gr1 high monocytes during shiga toxin‐induced HUS. We demonstrate that Ccr2 ‐deficient mice lack Gr1 high monocytes in the kidney during HUS and kidney injury was ameliorated in the absence of monocytes. Targeting monocytes during shiga toxin‐induced HUS might be a beneficial therapy during HUS.